STUDY ON IN PLANTA TRANSFORMATION IN MAIZE - Trình, Đinh Văn (Vietnam Journal of Biotechnology, 2011)
Almost fransformation methods in maize (Zea mays L.) require multiple tissue culture manipulations that are time-consuming and expensive. Furthermore, these only can apply to a few highly regenerative genotypes. The first time in Vietnam, we applied a simple in planta method that makes it possible to fransfer commercial variety  through  female  reproductive  system. The Agrobacterium tumefaciens sfrain  EHA105 which  contains plasmid pBig.ubi carrying drought tolerant gene - ZmDREBlA  and hygromycin resistant gene - hpt was used. Maize'  silks (female flowers) were isolated and applied with bacterium suspension before  pollinating with the pollens ofthe  same cultivars.  135 ears (13145 kemels) of  TQ harvested in the winter-spring crop 2006 - 2007. The fransgenic seedlings at 2 - 3 leaves state were selected by drought sfress. Hygromycin resistant assay and PCR  analysis  on  59 plants  (To) survived  after  drought  selection  showed  the transformation  efficiency  of TQ plants was 0.023%.